Body Mass Index and Body Fat Percentage Are Associated with Clinical Outcomes in Patients Receiving PD-1/PD-L1 Inhibitors: A Prospective Exploratory Study - Ángela Morell; Alberto Morell; Ainhoa Aranguren; Jacobo Rogado; Miguel Sampedro; Rebeca Mondéjar; Ramón Colomer; M. Paz Lorenzo; Esther Ramírez (Journal of Personalized Medicine, 2026)
Background/Objectives: Immunotherapy using immune checkpoint inhibitors has transformed the treatment of multiple solid tumours. However, the clinical response to programmed death receptor (PD-1) and its ligand (PD-L1) inhibitors remains heterogeneous. We have previously shown that host-related factors such as body mass index (BMI) may modulate the efficacy of immunotherapy. The aim of this study was to determine whether body composition, measured with bioelectrical impedance analysis (BIA) before treatment initiation, is a prognostic factor for survival outcomes in patients treated with PD-1/PD-L1 inhibitors, independently of tumour type and stage. Methods: In this prospective, single-centre observational study, patients with solid tumours underwent baseline body composition assessment using multifrequency bioelectrical impedance analysis (BIA) before initiation of PD-1/PD-L1 inhibitor therapy. Overall survival (OS), progression-free survival (PFS), and treatment-related adverse events were evaluated using Kaplan–Meier analyses and multivariable Cox regression models adjusted for tumour stage and metastatic status. Results: A total of 80 patients with solid tumours were included in the study. The median age was 67 years, and 48 (60.0%) were male. Higher BMI (≥25 kg/m2) and elevated body fat percentage (%BF) were associated with more favourable survival outcomes. After adjustment for tumour stage and metastatic status, BMI ≥ 25 kg/m2 was associated with a lower risk of death (HR 0.286, 95% CI 0.087–0.941; p = 0.039). Similar results were observed for elevated %BF (HR 0.289, 95% CI 0.087–0.963; p = 0.036). Neither BMI nor %BF was significantly associated with the occurrence of confirmed immune-related adverse events. Conclusions: Baseline BMI and body fat percentage were associated with survival outcomes in this exploratory cohort of patients receiving PD-1/PD-L1 inhibitors. These findings should be considered exploratory and hypothesis-generating and require confirmation in larger, tumour-specific prospective studies.